2021
DOI: 10.1111/1759-7714.13750
|View full text |Cite
|
Sign up to set email alerts
|

Thymic epithelial tumors: Do we know all the prognostic factors?

Abstract: Background Thymic epithelial tumors constitute a morphologically and clinically diverse group of rare neoplasm of the anterior mediastinum. Methods Here, we present an analysis of 188 patients diagnosed with primary thymic tumors between 1995 and 2015. The prognostic value of selected clinical and morphological factors was assessed in relation to overall survival and recurrence‐free survival. Results The risk of recurrence increased significantly in thymic carcinoma diagnosis (P = 0.0036), co‐occurrence of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…In our study, the cut-off time was 2020-12-31, and therefore, the 2015 WHO histological classification system was used in this study. Our results demonstrated that this classification was associated with the OS of TET patients, but was not an independent prognostic factor by Cox multivariate survival analysis, which was consistent with previous studies ( 33 , 34 ). An increased WHO histological grade showed more malignant behavior and was associated with a poor prognosis ( 33 ).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the cut-off time was 2020-12-31, and therefore, the 2015 WHO histological classification system was used in this study. Our results demonstrated that this classification was associated with the OS of TET patients, but was not an independent prognostic factor by Cox multivariate survival analysis, which was consistent with previous studies ( 33 , 34 ). An increased WHO histological grade showed more malignant behavior and was associated with a poor prognosis ( 33 ).…”
Section: Discussionsupporting
confidence: 92%
“…Secondly, there is marked interobserver variation when assigning the histological subtypes in human TET (Dawson et al ., 1994, Detterbeck, 2006, Verghese et al ., 2008). Nevertheless, most human studies show that thymic carcinoma has the worst survival, but whether this has independent prognostic significance is unclear (Kondo et al ., 2004, Rea et al ., 2004, Rieker et al ., 2008, Weissferdt & Moran, 2015, Knetki‐Wróblewska et al ., 2021). These histologic subtypes have not demonstrated prognostic significance in dogs (Burgess et al ., 2016; Yale et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 8 studies [8][9][10][11][12][14][15][16] explored the relationship between tumor size and patient OS included 3163 patients. Pooled results (Fig.…”
Section: Prognostic Impact Of Tumor Size On Osmentioning
confidence: 99%
“…The study characteristics of the 9 recruited articles are summarized in Table 1. HRs with 95% CIs regarding tumor size on OS could be obtained from 8 studies [8][9][10][11][12][14][15][16] directly and HRs with 95% CIs regarding tumor size on RFS could be obtained from 6 studies [8,[10][11][12][13]15] directly. Of the 9 studies we included, the study by Liu et al [14] was only on TC, the study by Okumura et al [13] was only on thymoma, and the other 7 studies were on TETs (both thymoma and TC).…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation